Performative journalism and its contribution to the narrative crisis in museums: The case of the Maritime Museum of Mallorca in the fishermen’s quarter of Molinar - Gayà Morlà, Catalina; Seró Moreno, Laia; Garde Cano, Cristina; Vidal Castell, David (Anàlisi, 2025)
Within the context of crisis in the cultural narrative faced by institutions such as museums, performative journalism acts as a methodology to challenge the narratives of domination that continue to occur but urgently need revision. This article shows how the connection between a museum and the communicative action enabled by performative journalism establishes the institution not just as a guardian of intangible heritage but also an agent that recognises that cultural narrative is a political action for transformation. The first part of the article argues that performative journalism – as ethnographic activity – acts as a mediator for the restitution of collective memory through the articulation of memory and communal practices. In the second part, the results of a pioneering initiative of performative journalism linked to the activity of a museum, the Maritime Museum of Mallorca (MMM), are presented. The conclusion summarises how performative journalism addresses the crisis of access, participation and cultural narrative that museums face.